The influence of career planning towards insurance agents’ strategy for career satisfaction - Tan, Fee Yean; Yahya, Khulida Kirana (2011)
The present research reports on the influence of career planning and career strategy on insurance agents’ career satisfaction. 531 full-time insurance agents located at the northern state of Peninsular Malaysia participated in this research. Controlling for gender, marital status, education, age and income, research found that awareness of self and environment were positively related to career strategy and career satisfaction. Goal-setting had a positive relationship with career strategy and a negative influence on career satisfaction. The results further indicated that career strategy partially mediate the relationship between awareness of self and environment and career satisfaction. The theoretical and practical implications of these findings were also discussed.